2018
DOI: 10.1080/14767058.2017.1387888
|View full text |Cite
|
Sign up to set email alerts
|

Meconium microbiome as a new source of information about long-term health and disease: questions and answers

Abstract: Diversified intrauterine microbiome may modify the environment of the developing fetus with possible short- and long-term impact on the individual's health and disease. Meconium which provides the individual-specific information about the intrauterine microbiome composition is a biological material with potential uses in routine clinical diagnostic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Since meconium is a biological material formed during the gestation, it has been considered a very useful source of information that reflects the in utero microbial environment. 16 The findings presented in this brief report indicate that almost all meconium samples were colonized; thus it can be assumed that neonates' meconium may have bacterial DNA prior to birth. It has been reported that mothers can be responsible for the transference of (some) these microbes to the fetus, as well as their metabolites and other molecules that shape the offspring's innate immune system.…”
Section: Discussionmentioning
confidence: 74%
“…Since meconium is a biological material formed during the gestation, it has been considered a very useful source of information that reflects the in utero microbial environment. 16 The findings presented in this brief report indicate that almost all meconium samples were colonized; thus it can be assumed that neonates' meconium may have bacterial DNA prior to birth. It has been reported that mothers can be responsible for the transference of (some) these microbes to the fetus, as well as their metabolites and other molecules that shape the offspring's innate immune system.…”
Section: Discussionmentioning
confidence: 74%
“…Other researchers have reported similar results, associating CS with the risk of overweight in children [65,66]. These results could indicate the relevance of priority events in infant health, including those altering microbial colonization, , thereby supporting the early programming hypothesis [67,68]. Researchers have described how antibiotic therapy during early life modulates weight gain in different ways depending on the antibiotic dose in both animal [69] and human epidemiological studies [66].…”
Section: Discussionmentioning
confidence: 63%
“…It is possible that minor proteases of microbial origin can participate in degrading the 33-mer. Previous studies have shown that a specific microbiota is present in human meconium [ 13 ]. Moreover, it has been described that maternal commensal microbiota presented to the fetus during the last trimester of pregnancy contribute to the establishment of oral tolerance [ 14 ].…”
Section: Discussionmentioning
confidence: 99%